Ultrafast mid-infrared optics in gas-filled hollow core fiber - Deng, Ang (Nanyang Technological University, 2023)
Mid-infrared (MIR) spectral region shows great technical and scientific potential because most molecules interact strongly with photons in this range. The spectral feature, or fingerprint, that is unique to each specific molecule can be identified using MIR light. The ultrafast lasers emitting in the MIR region and MIR supercontinuum (SC) sources can find wide implications in many areas such as telecommunications, microscopy, optical coherence tomography and medicine. The bottleneck is the current lack of powerful and reliable ultrafast MIR lasers that can efficiently drive these applications. A common solution to generate ultrafast MIR pulses rely on the optical parametric process in nonlinear crystals, but its performance is sensitive to environmental variations. Fiber-based systems have the advantage in this regard. However, silica—the commonly used material for optical fibers—is not transparent beyond 2.4 μm. A recent progress made in mode-locked lasers incorporating compound-glass yielding nanojoule level pulses marks a breakthrough in the ultrafast MIR light source development. One alternative approach is to utilize gas-filled hollow core fiber (HCF). Since the light is tightly confined in the fiber central hollow region, HCF offers a much higher damage threshold than solid core fiber, making it suitable for high-power beam delivery. The core modes in HCF allow it to bypass high absorption in silica and provide HCF with low transmission loss in the MIR region. Furthermore, HCF can be filled with different types of gas, which makes it possible to easily and precisely pressure tune the fiber non-linearity and dispersion. With all these attractive properties, gas-filled HCF presents an excellent platform for ultrafast MIR non-linear studies. Among various types of HCFs, anti-resonant hollow core fiber (AR-HCF) offers wide transmission bandwidth with relatively low loss, and therefore it has been widely studied and adopted in recent years. The light-guiding properties of AR-HCFs depend significantly on the cladding structure. To understand the influence of the cladding geometry on the fiber performance in the MIR region, we carry out comprehensive numerical studies on few key structural parameters of AR-HCFs—dielectric wall thickness of cladding elements, core diameter, and core-cladding curvature—in view of MIR beam delivery. We find that a resonance-like band with a high loss peak and oscillating group velocity dispersion (GVD) appears in the long-wavelength limit of the first transmission band in AR-HCF. This resonance also follows the anti-resonant reflecting optical waveguide (ARROW) model. This indicates that the dielectric wall thickness of the cladding elements must be at least one-eighth of the operating wavelength to ensure low loss and stable GVD guidance. Moreover, we observe that there is an optimal cladding tube size to core ratio in AR-HCF with a given number of cladding elements. This is governed by the combined effect of the mode index mismatch and mode field overlap integral between the core mode and cladding modes. We also reveal that loss becomes more strongly dependent on the core size to wavelength ratio when the cladding tube size is at its optimum. We experimentally demonstrate microjoule-level MIR femtosecond pulse generation in gas-filled HCFs. Namely, we exploit the guiding mechanism of AR-HCFs to introduce phase-matched conversion of 2 μm pump to a transmission band edge of the fiber in the 3–4 μm region. The pump is deliberately chosen at 2 μm, considering the rapid advances in high-performance ultrafast fiber lasers at this wavelength. The MIR emerges from the fiber output with the single pulse energy exceeding 1 μJ, which translates to a peak power in the tens of megawatts range. The conversion efficiency from the 2 μm pump to the MIR region is up to 9.4 %. This phased-match induced frequency down-conversion utilizes the band-edge effect in AR-HCF. The wavelength of generated emission is governed solely by a structural parameter of the AR-HCF—dielectric wall thickness of the cladding elements. This is confirmed by employing another fiber that has different cladding wall thickness to shift the wavelength of the MIR radiation. Other parameters like gas pressure and input pulse energy play negligible role in determining the wavelength but alter the conversion efficiency, which offers the possibility to power scale the MIR output. This technique opens an avenue to high-power femtosecond MIR fiber laser with near-diffraction-limited output beam quality and exceptional stability. Gas-filled HCFs also offer the opportunity for generating supercontinuum (SC) light in the MIR region. We report SC generation in gas-filled AR-HCFs with the bandwidth spans more than four-octave covering the 0.25–4.7 μm region. This is achieved by pumping argon-filled AR-HCFs with 65 fs pulses at 2 μm. The achieved bandwidths are slightly different depending on the geometry of the AR-HCF used, due to the differences in the MIR transmission properties of the fibers. The differences are caused by the fiber different dielectric wall thickness of cladding elements and core diameter, which places a long-wavelength limit on the transmission window for silica-based AR-HCFs. This doctoral thesis studied and demonstrated the high-power ultrafast MIR sources and SC generation in gas-filled HCFs. These techniques present a new pathway to build all fiber-based ultrafast MIR light sources or SC sources. They can offer numerous advantages such as reliability, small footprint, and excellent spatial beam quality while still maintaining the level of output power offered by conventional non-linear crystal parametric systems.